Proposed Mitigation and Adaptation Strategies Related to Climate Change: Guidance for OEM Professionals. Issue 9 (September 2021) - Nabeel, Ismail; Caraballo-Arias, Yohama; Perkison, William Brett; McCarthy, Ronda B.; Saberi, Pouné; Berenji, Manijeh; Goldman, Rose H.; Laestadius, Jasminka Goldoni; Sokas, Rosemary K.; Das, Rupali; Senay, Emily; Wilkenfeld, Marc; et al.
Abstract : N/A: Climate change is an urgent challenge amplified by socioeconomic factors that demands thoughtful public health responses from OEM professionals. This guidance statement from the American College of Occupational and Environmental Medicine focuses on the different strategies that these health professionals can implement to protect workers from health impacts associated with climate change hazards, foster workplace resilience in the face of rapidly changing environments, and take the necessary steps to mitigate the effects of global climate change.